UPAYA PENANGANAN STUNTING MELALUI ECOUNSELING DENGAN PENDEKATAN INKLUSI DI RURAL AREA - Sari, Ignasia Yunita; Diah Pujiastuti; Nining Indrawati; Indah Prawesti; Ethic Palupi; Santahana Febriyanti (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Stunting is a serious threat to the future generation of Indonesia. Stunting is a growth and development disorder resulting from chronic malnutrition and recurring infections. Posyandu is the front line in efforts to prevent stunting because it involves measuring growth and development. The aim of this Community Service (PKM) is to address stunting through e-counseling with an inclusive approach to promote and support the participation of people with disabilities and their access to healthcare services. It is expected that this PKM will contribute to the sustainability of community-based health programs that are inclusive. From the PKM conducted, various characteristics of the cadres were identified, including those who areve. E-counseling is conducted both offline and online. The offline e-counseling activities for cadres proceeded smoothly, with all participants enthusiastically participating in every training process. One of the cadres is inclusive. There was an increase in knowledge by 6 points. The offline e-counseling activities for mothers with stunted toddlers went well. The online e-counseling activities for one month also went well, although one participant experienced signal issues.